Emergence of low-energy electronic states in oxygen-controlled Mott insulator Ca2RuO4+δ. (March 2021) - Miyashita, Takeo; Iwasawa, Hideaki; Yoshikawa, Tomoki; Ozawa, Shusuke; Oda, Hironoshin; Muro, Takayuki; Ogura, Hiroki; Sakami, Tatsuhiro; Nakamura, Fumihiko; Ino, Akihiro
Abstract: Insulator-to-metal transition in Ca2 RuO4 has drawn keen attention because of its sensitivity to various stimulation and its potential controllability. Here, we report a direct observation of Fermi surface, which emerges upon introducing excess oxygen into an insulating Ca2 RuO4, by using angle-resolved photoemission spectroscopy. Comparison between energy distribution curves shows that the Mott insulating gap is closed by eV-scale spectral-weight transfer with excess oxygen. Momentum-space mapping exhibits two square-shaped sheets of the Fermi surface. One is a hole-like α sheet around the corner of a tetragonal Brillouin zone, and the other is an electron-like β sheet around the Γ point. The electron occupancies of the α and β bands are determined to be n α = 1 . 6 and n β = 0 . 6, respectively. Our result indicates that the insulator-to-metal transition occurs selectively in d x z and d y z bands and not yet in d x y band. This orbital selectivity is most likely explained in terms of the energy level of d x y, which is deeper for Ca2 RuO 4 + δ than for Ca1.8 Sr0.2 RuO4 . Consequently, we found substantial differences from the Fermi surface of other ruthenates, shedding light on a unique role of excess oxygen among the metallization methods of Ca2 RuO4 . Highlights: Direct observation of the Fermi surface emerging from a ruthenate Mott insulator. Metallic electronic states can be induced by a small amount of excess oxygen. Our result opens a new way to understand and control the metal–insulator transition.